Childhood Obesity and Respiratory Diseases: Which Link? - Emanuela di Palmo; Emanuele Filice; Alessandra Cavallo; Carlo Caffarelli; Giulio Maltoni; Angela Miniaci; Giampaolo Ricci; Andrea Pession (MDPI AG, 2021)
Prevalence of childhood obesity is progressively increasing, reaching worldwide levels of 5.6% in girls and of 7.8% in boys. Several evidences showed that obesity is a major preventable risk factor and disease modifier of some respiratory conditions such as asthma and Obstructive Sleep Apnea Syndrome (OSAS). Co-occurrence of asthma and obesity may be due to common pathogenetic factors including exposure to air pollutants and tobacco smoking, Western diet, and low Vitamin D levels. Lung growth and dysanapsis phenomenon in asthmatic obese children play a role in impaired respiratory function which appears to be different than in adults. Genes involved in both asthma and obesity have been identified, though a gene-by-environment interaction has not been properly investigated yet. The identification of modifiable environmental factors influencing gene expression through epigenetic mechanisms may change the natural history of both diseases. Another important pediatric respiratory condition associated with obesity is Sleep-Disordered Breathing (SDB), especially Obstructive Sleep Apnea Syndrome (OSAS). OSAS and obesity are linked by a bidirectional causality, where the effects of one affect the other. The factors most involved in the association between OSAS and obesity are oxidative stress, systemic inflammation, and gut microbiota. In OSAS pathogenesis, obesity's role appears to be mainly due to mechanical factors leading to an increase of respiratory work at night-time. However, a causal link between obesity-related inflammatory state and OSAS pathogenesis still needs to be properly confirmed. To prevent obesity and its complications, family education and precocious lifestyle changes are critical. A healthy diet may lead to an improved quality of life in obese children suffering from respiratory diseases. The present review aimed to investigate the links between obesity, asthma and OSAS, focusing on the available evidence and looking for future research fields.